(The Role of Chocolate as healthy Food products and Its Possibility Product Development as Functional Food in the Food Industry) - Sudibyo, Agus (Balai Besar Industri Agro, 2010)
Cocoa-derivatives (cocoa powder,chocolate,cocoa related products) have been known for hundred of years. these products were consumed all over the world and were largely studied due to their significant content of phytochemicals (procyanidin,flavonoids,catechin,epicaechin)with great healt effects.recent scientific articels showed that the high quality and quantity of antioxidants and chocolate and the flavonoids content in cocoa are able to reduce the number of radicals in the body that contribute to medical problems,such as cardiovascular diseases and cancer. they can also act as anti-aging. the objectives of this paper are:(1) to prepare a scientific information for scientists and researchers in exploration on R&d of food products diversification based on cacao as health food;(2)to prepare an information for R&D institutions in developing more comprehensive understading of intractions that occur among cocoa derived foods,medicines and dietary supplement;and(3)to prepare an information for society to increase their interest in cocoa and chocolate consume with better understanding of theirs benefits and weakness as health food product.this article studied a brife review of the potential strength of cocoa and chocolate and its effects on healts and the weakness of cocoa and chocolate products as health food products,also its possibility product development as functional food in the food industry.